The Gig Economy in India : Start-Ups, Infrastructure and Resistance. - Thomas, Pradip (Routledge, 2024)
The Gig Economy in India explores the topic of gig work in India's digital political economy, and the relationship between key factors such as start-ups, state governments, and platform providers. The book begins by placing the gig economy in context, defining the platform ecosystem and the Indian government's perception of its problems and opportunities. Thomas then examines the critical dimensions of the gig economy in India, from its data infrastructure capabilities, the enabling role of venture capitals and FinTech, to government regulations. Attention is paid to the precarity of gig labour, the vagaries of algorithmic management, and the minimal legal support available for workers. The book also includes chapters on labour resistance and highlights some of the issues related to the ethics of artificial intelligence. Given the limited research on India as a case study, this volume fills a crucial gap in the literature. It will interest scholars in diverse fields such as business management, digital media, and communication studies.
Keywords: Gig economy -- India.; Part-time employment -- India.; Flexible work arrangements -- India.; elektronické knihy; electronic books